KREATIVITAS GURU IPS DALAM INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL BUGIS PADA PEMBELAJARAN IPS - Hasni, Hasni; Jumadi, Jumadi; Najamuddin, Najamuddin; Supriatna, Nana; Sapriya, Sapriya; Holilah, Mina (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2024)
Teacher creativity in teaching character education values is very important, especially in local contexts that are rich in cultural wisdom. This study aims to determine the creativity of social studies teachers in integrating character education values based on Bugis local wisdom into learning. This type of research uses a qualitative approach with a case study method at SMP Negeri 2 Makassar. Data were collected through observation, in-depth interviews with social studies teachers, and document analysis related to learning based on Bugis local wisdom. The data source comes from SMP Negeri 2 Makassar which has a Bugis cultural background. The results showed that the creativity of social studies teachers in integrating character education values based on Bugis local wisdom into social studies learning is to use a variety of creative methods, such as the use of Bugis folklore, traditional simulations, research projects on local culture, the use of digital visual media, environmental contextual learning, and developing character attitudes and behaviors proved effective in this study. The conclusion is that social studies teachers play a key role in internalizing Bugis local wisdom values into learning. Therefore, it is important for schools and the government to continue to support the development of teachers' creativity in integrating local wisdom into the curriculum